2000
DOI: 10.1209/epl/i2000-00233-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability in nanocrystalline ZnO

Abstract: The grain-size effect on phase transition induced by pressure in ZnO nanocrystals has been investigated by in situ high-pressure synchrotron radiation X-ray powder diffraction, optical and electrical resistance measurements. The transition pressure of the B4-to-B1 phase transformation for 12 nm ZnO is found to be 15.1 GPa while it is 9.9 GPa for bulk ZnO. Three components: the ratio of the volume collapses, the surface energy difference, and the internal energy difference, governing the change of transition pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
116
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 22 publications
21
116
0
Order By: Relevance
“…11͒ indicate that both forward and backward pressure transitions are particle-size dependent. In a same manner, Jiang et al 14 found an enhancement of the upstroke transition pressure ͑15.1 GPa͒ in 12͑2͒ nm size ZnO nanocrystals compared to the bulk value. After a decompression from 52.5 GPa down to ambient pressure, a coexistence of the w and c phases was recovered with a large fraction of the NaCl phase.…”
mentioning
confidence: 71%
“…11͒ indicate that both forward and backward pressure transitions are particle-size dependent. In a same manner, Jiang et al 14 found an enhancement of the upstroke transition pressure ͑15.1 GPa͒ in 12͑2͒ nm size ZnO nanocrystals compared to the bulk value. After a decompression from 52.5 GPa down to ambient pressure, a coexistence of the w and c phases was recovered with a large fraction of the NaCl phase.…”
mentioning
confidence: 71%
“…Although it shows a rather large hysteresis it was found to be fully reversible. Other studies, however, report the persistence of a large fraction of the NaCl phase after complete pressure release (Bates et al, 1962;Recio et al, 1998;Jiang et al, 2000). Further experimental studies of the wur→NaCl transition in ZnO have been reported by Gerward and Olsen (1995), Karzel et al (1996), Desgreniers (1998), andKusaba et al (1999).…”
Section: Znomentioning
confidence: 94%
“…6 It has also been recently found that ZnO nanocrystals undergo the wurtzite to rocksalt (NaCl) structural transition at a much higher applied pressure (~15 GPa) than that for the bulk (9.0±0.5 GPa). 7 Pressure induced hysteresis has also been observed: structurally transformed ZnO nanocrystals are found to retain the metastable NaCl phase at ambient conditions. 8 So far there have been no reported experimental investigations of the optical properties of ZnO nanocrystals under high pressure to the best of our knowledge.…”
mentioning
confidence: 96%
“…These observations are consistent with previous work showing that nanocrystalline ZnO has its wurtzite to rocksalt phase transition at a higher pressure (15.0 GPa) as compared to the bulk value (9.0±0.5 GPa) and that pressuretransformed ZnO is metastable in the PL-inactive rocksalt phase at ambient pressure. 7,8 The change of the band-edge luminescence peak energy of the ZnO nanowires together with the green emission band is displayed in Fig. 3 as a respectively.…”
mentioning
confidence: 99%